PHP CLI Create Command Line Interface Scripts with PHP - Aley, Rob (Apress : Imprint: Apress, 2016)
This concise book shows you how to create PHP Command Line Interface (CLI) scripts, including user interaction and scripts to automate and assist your workflow. Learn to quickly create useful and effective Command Line software and scripts using the world's most popular web scripting language, PHP. Enjoy the benefits of writing CLI scripts in PHP: Save money by redeploying existing skills, not learning new ones. Save time and increase productivity by using a high-level language. Make money by providing your clients with a full-stack service. With PHP CLI readers will: Learn about the PHP CLI SAPI Discover how to use it to run PHP scripts off-line Easily deal with user input and console output Work with helper libraries and software Find out the differences between programming for the web and for the CLI.